From Law to Spirituality: Al-Ghazali’s Contribution to the Concept of Religious Moderation - Rosidi, Rosidi; al-Akiti, Muhammad Ayman; Varyda, Vateen Nayla Nurul (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This study aims to explore how the concept of religious moderation is implicitly embedded in the kitab kuning, particularly within the fiqh-sufistic thought of Imam al-Ghazali. Unlike conventional fiqh, which focuses primarily on vertical obligations to God, al-Ghazali integrates external legal observance with internal spiritual ethics, establishing a comprehensive framework that connects ritual devotion with social responsibility. Methodologically, this research employs qualitative library research using Bidayat al-Hidayah and Ihya’ ‘Ulum al-Din as primary sources, analyzed through content analysis to identify ethical and social patterns that reflect moderation. The findings reveal twenty-three ethical principles formulated by al-Ghazali, encompassing aspects such as companionship (al-shuhbah), social etiquette, and moral conduct, all of which promote equality, inclusivity, and communal harmony. Theoretically, this study contributes to the discourse on Islamic ethics and moderation by situating al-Ghazali’s fiqh-sufistic synthesis as an epistemological foundation for contextualizing religious behavior in plural societies. The originality of this research lies in its reinterpretation of classical Islamic ethics as practical indicators of religious moderation in the Indonesian context, offering new insights for curriculum development in pesantren, deradicalization programs, and civic education. While limited by its textual scope and lack of empirical validation, this study provides a theoretical basis for future field research examining the application of al-Ghazali’s ethical framework in modern educational and social environments.